Corpus Methodologies in Literary Translation Studies: An Analysis of Speech Verbs in Four Spanish Translations of Hard Times - Ruano, Pablo (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2017)
In this article, speech verbs in Dickens’s Hard Times (1854) and their translation into Spanish are analyzed. Apart from their basic function of introducing speech, these verbs can also contribute to characterization. The regular occurrence of a particular speech verb to report the direct speech of a particular character helps to create a fictional personality. Given the important role they may play, the rendering of such verbs in four Spanish versions of this novel is assessed. To do so, a corpus-based methodology has been employed. A concordancing software was used to retrieve speech verbs from the original novel, allowing their close analysis in context. Then, using an aligned parallel corpus containing the four versions, a comparison was carried out to see how they have been rendered. Evidence is provided that none of the four translations entirely preserves the characterizing value of the verbs, which may affect the way readers form impressions of characters in their minds. The use of this corpus metholodogy is thus seen to contribute to the field of literary translation studies.